PENGARUH EFEK KOMUNITAS, KUALITAS PRODUK, DAN VARIASI PRODUK TERHADAP BRAND AWARENESS PADA NARSS MAKE-UP ARTIST TULUNGAGUNG - Nareswary Nur Allamah; Umi Nadhiroh; Udik Jatmiko (Cahaya Ilmu Bangsa, 2024)
This research aims to determine the influence between community effects, product quality and product variety on brand awareness. The research method used is a quantitative method with a descriptive approach. Data collection in this research was carried out by distributing questionnaires to Narss Makeup Artist Tulungagung clients and calculated using the SPSS Version 25 application. Data analysis techniques used included Validity Test, Reliability Test, Classic Assumption Test, Multiple Linear Regression Analysis, T Test, F Test , and Test of the Coefficient of Determination R2. In the validity test, it is known that all statement items on the variables (X1, X2, Then in the reliability test it was discovered that each variable had a Cronbach's Alpha value > 0.60, so the variable was declared reliable. Furthermore, in the t test it is known that all variables (community effect, product quality, product variety) have a positive value and the significance is <0.05 so that it is stated that they partially have a significant effect on brand awareness. Then in the F test it is known that the Sig value. for all variables together it is 0.000 < 0.05 and the value of Fcount > Ftable, it can be concluded that the variables of community effect, product quality and product variety simultaneously influence brand awareness at Narss Makeup Artist Tulungagung.